Pertumbuhan dan Laju Sintasan Krablet Kepiting Bakau (Scyla serrata) dengan Pemberian Jenis Pakan Rucah yang Berbeda - Suharyanto Suharyanto (Fakultas Biologi | Universitas Jenderal Soedirman, 2012)
The aim of this experiment was to find out information on suitable trash fish for the growth and survival rate of mud crabs (Scyla serrata). The research was conducted in Marana Brackishwater pond research station of the Research Institute for Coastal Aquaculture, Maros, South Sulawesi for 28 days. Twelve aquaria of 60 x 40 x 40 cm3 were used in this experiment using Completely Randomized Design. Treatments tested were four differents species of trash fishes i.e. A; sibula (Sardinella sp), B; tembang (Clupea sp), C; Anchovy (Stolephorus sp) and D; Tilapia (Tilapia mosambica), each with three replications. Twentyfive pieces of crablets of 5,9 + 0,2 mm in carapace width and 0,06 + 0,02 g in body weigth were stocked in each aquarium. Crablets were then fed with trash fish with the dosage of 15% of total biomass per days given twice a day. The results showed that the growth of crablets fed with tilapia was the best trash fish (P>0.05), among the treatments which were tested. The use of other fishes were not significantly different (P>0.05) on the crablet growth.